2015
DOI: 10.1128/aem.02752-15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Listeria monocytogenes inlA Alleles Prone to Phase Variation and inlA Alleles with Premature Stop Codon Mutations among Human, Food, Animal, and Environmental Isolates

Abstract: cIn Listeria monocytogenes, 18 mutations leading to premature stop codons (PMSCs) in the virulence gene inlA have been identified to date. While most of these mutations represent nucleotide substitutions, a frameshift deletion in a 5= seven-adenine homopolymeric tract (HT) in inlA has also been reported. This HT may play a role in phase variation and was first identified among L. monocytogenes lineage II ribotype DUP-1039C isolates. In order to better understand the distribution of different inlA mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 41 publications
(82 reference statements)
6
30
1
Order By: Relevance
“…monocytogenes have been published, and several types of PMSCs have been described [412]. There is less information on inlA alleles in strains from environmental origins, but those published studies indicate that inlA alleles predominantly are intact both in healthy ruminants [8], and farm animals and their environments [10, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…monocytogenes have been published, and several types of PMSCs have been described [412]. There is less information on inlA alleles in strains from environmental origins, but those published studies indicate that inlA alleles predominantly are intact both in healthy ruminants [8], and farm animals and their environments [10, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that inlA PMSC mutations are responsible for attenuated virulence in L . monocytogenes isolates (Manuel et al, ; Nightingale et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The inlA gene encodes a product that is responsible for the entry of the bacterium into the host cell, and genes inlB, inlC, and inlJ are directly involved in the subsequent infection stages (Doumith et al, 2004;Liu et al, 2007). Some studies showed that inlA PMSC mutations are responsible for attenuated virulence in L. monocytogenes isolates (Manuel et al, 2015;Nightingale et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria monocytogenes can be categorized into genetic lineages (Manuel et al . ), which are serotype specific. Lineages I and II contain serotypes generally associated with human listeriosis; serovars 1/2b and 4b group in lineage I, and serovars 1/2a and 1/2c in lineage II (Hain et al .…”
Section: Introductionmentioning
confidence: 99%